A Novel Vector for Construction of Markerless Multicopy Overexpression Transformants in Pichia pastoris - Li, Ding; Zhang, Bo; Li, Shuting; Zhou, Jie; Cao, Hui; Huang, Yan; Cui, Zhongli (Frontiers in Microbiology, 2017)
Pichia pastoris is widely used as a platform for heterologous protein expression because of its high volumetric productivity. Multicopy integration of the target gene is commonly used to improve the production of the target protein. Cre/lox recombination system is a powerful tool for the marker rescue during multiple integrations with one selection marker. Here we reported a novel expression vector based on the Cre/lox recombination system for multiple integrations of target gene to construct multicopy expression strain of P. pastoris. PAOX1 promoter was fused to cre to construct a methanol inducible Cre recombinase. The leakage expression of Cre recombinase in Escherichia coli was blocked by introducing the operator gene lacO. The expression vector designed pMCO-AOXα was stable in E. coli and could effectively rescue the Zeocin resistance gene for next round of integration in P. pastoris. Phytase AppA from E. coli was chosen as a reporter gene. Transformants with 2–16 copies of appA were constructed by using a single antibiotic. Expression of appA was gene dosage dependent when <12 copies were integrated. The protein yield increased 4.45-folds when 12 copies of appA were integrated comparing with the single copy integration. Our results showed that pMCO-AOXα was highly effective for rational construction of multicopy transformat in P. pastoris.